Sustainability of the Tourism Industry, Based on Financial Key Performance Indicators - Adriana Dutescu; Adriana Florina Popa; Andreea Gabriela Ponorîca (Amfiteatru Economic)
Even if there is a real need of a set of key performance indicators for small and medium sized enterprises, this is not yet considered to be satisfied. Our research is focused on two main aspects, each of them individually important for the users of accounting information: the basic indicators specific for analysing operational performance and for decision making and the trend of the key performance indicators in the context of the economic crisis. The starting point of the study is a questionnaire addressed to small and medium sized enterprises activating in the tourism area, especially in the hotel industry. The respondents answered the questions in perfect anonymity by choosing one of the multiple choices for some of them and offering open answers to the others. Our analysis reveals a fair view of the dynamic of the most used key performance indicators in Romanian hotel industry, the limits of their interpretation and usage and the evolution of the financial and economic performance. The declared purpose of the research is to set the bases of a starting point in order to provide solutions for improving the relevance and the usage of these indicators in this domain, in the context of a sustainable business, taking into account the nowadays status of the economy in general and in particular the hotel industry.